Silver treasures from the land of Sheba regional Yemeni jewelry - Ransom, Marjorie (The American University in Cairo Press, 2014)
""Silver Treasures from the Land of Sheba documents a disappearing artistic and cultural tradition with over three hundred photographs showing individual pieces, rare images of women wearing their jewelry with traditional dress, and the various regions in Yemen where the author did her field research. Ransom's descriptions of the people she met and befriended, and her exploration of the significance of a woman's handmade jewelry with its attributes of power, protection, beauty, and personal identity, will appeal to ethnic jewelry fans, ethnographers, jewelry designers, and art historians. Amulet cases, hair ornaments, bridal headdresses, earrings, necklaces, ankle and wrist bracelets are all beautifully photographed in intricate detail, interspersed with the author's own photographs of the women who shared their stories and their hospitality with her. A chapter on the history of silversmithing in Yemen tells the surprising story of the famed Jewish Yemeni silversmiths, many of whom left Yemen in the late 1940s. This is the first in-depth study of Yemeni silver, uniquely illustrated with photographs of a world that is transforming before our eyes, and animated with the portraits of a precious legacy.""--